ART THERAPY-AS A MODERN DIRECTION IN SCHOOL ACTIVITIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The importance and functions of art therapy. To study the importance of the use of art therapy in schoolchildren.